2017
DOI: 10.1136/jramc-2017-000815
|View full text |Cite
|
Sign up to set email alerts
|

UK Role 4 military infectious diseases and tropical medicine cases in 2005–2013

Abstract: UK service personnel in significant numbers continue to suffer a wide range of infectious diseases, acquired throughout the globe, which often require specialist tertiary infection services to diagnose and manage. Future prospective data collection is recommended to identify trends, which in turn will inform military training needs and future research priorities in the Defence Medical Services (DMS) and allows development of appropriate policies and clinical guidelines for management of DMS personnel with infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Infectious diseases have long been a significant cause of morbidity and mortality to the British military 3. Previous data have demonstrated that, second to infective gastroenteritis, UFI presented a significant caseload for deployed MTFs in both Iraq4 and Afghanistan,5 as well as at Role 4 6. The recent response to the Ebola crisis in West Africa demonstrated that UFI continues to be a significant reason for admission 7.…”
Section: Discussionmentioning
confidence: 99%
“…Infectious diseases have long been a significant cause of morbidity and mortality to the British military 3. Previous data have demonstrated that, second to infective gastroenteritis, UFI presented a significant caseload for deployed MTFs in both Iraq4 and Afghanistan,5 as well as at Role 4 6. The recent response to the Ebola crisis in West Africa demonstrated that UFI continues to be a significant reason for admission 7.…”
Section: Discussionmentioning
confidence: 99%
“…UK personnel have recently deployed to Iraq, Afghanistan, Sierra Leone, South Sudan and many other tropical regions of the world, with diseases endemic to each of these areas being represented in referrals to the UK military’s Role four infectious diseases and tropical medicine service 13. Diseases such as malaria, infectious gastroenteritis and cutaneous leishmaniasis remain prevalent during current contingency operations 14.…”
Section: Epidemiologymentioning
confidence: 99%
“…In addition, moving location means people are exposed to new endemic diseases, for which individual immunity is less likely. However, British military personnel deployed to unfamiliar locations with no inherent resistance or tolerance have a low rate of malaria infection,13 demonstrating that prevention can be effective in reducing disease during population movement.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation